Coating, coating preparation method and application method

By applying coatings of modified acrylic resin and other components on the surface of the nickel-plated diamond wire and curing ultraviolet light, the coating is formed to improve hydrophilicity, and the problem of insufficient liquid-plated diamond wire is solved, and the effect of reducing the amount and cost of the cutting liquid component is achieved.

CN119613995APending Publication Date: 2025-03-14JINWAN GAOJING SOLAR ENERGY TECH CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411883666.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The hydrophobicity of the nickel-plated diamond wire surface affects its liquid-carrying ability, reduces the effect of cutting liquid, resulting in problems of difficulty in defoaming and high cost.

Method used

Using a coating, including modified acrylic resin, 2-hydroxyethyl methacrylate, 1-hydroxycyclohexylphenyl ketone, plant polyphenols, nanocellulose and ethyl acetate, a coating is formed to enhance hydrophilicity by coating on the surface of the nickel-plated diamond wire and ultraviolet curing.

Benefits of technology

The hydrophilicity of nickel-plated diamond wire is improved, thereby enhancing its liquid-carrying ability, reducing the amount of wetting agent and defoaming agent in the cutting liquid, reducing costs and solving the problem of defoaming difficulty.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613995A_ABST
    Figure CN119613995A_ABST
Patent Text Reader

Abstract

The invention provides a coating, a coating preparation method and an application method, and relates to the technical field of monocrystalline silicon production. The coating provided by the invention is prepared from modified acrylic resin, 2-hydroxyethyl methacrylate, 1-hydroxycyclohexyl phenyl ketone, plant polyphenol, nano cellulose and ethyl acetate, the mass percent of the modified acrylic resin is 0.1%-3%, the mass percent of the 2-hydroxyethyl methacrylate is 0.1%-3%, the mass percent of the 1-hydroxycyclohexyl phenyl ketone is 2%-3%, the mass percent of the plant polyphenol is 0.1%-1%, the mass percent of the nano cellulose is 0.1%-1%, and the balance is water. The mass percent of the ethyl acetate is 89%-97.6%. The invention provides a coating, a coating preparation method and an application method. The hydrophilicity of a diamond wire can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of single crystal silicon production, and in particular to a coating, a preparation method and an application thereof. Background Art

[0002] In the prior art, in the process of processing single crystal silicon rods into silicon wafers, diamond wires are generally used in combination with cutting fluids. In order to ensure the stability of the diamond wires, the diamond wires are plated with metal nickel for reinforcement during the preparation process. Therefore, the diamond wires present a hydrophobic surface. However, this affects the ability of the diamond wires to carry fluids and reduces the effect of the cutting fluids. Therefore, how to improve the hydrophilicity of nickel-plated diamond wires is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention

[0003] In order to solve at least one of the problems mentioned in the background technology, the present invention provides a coating, a coating preparation method and an application method, which can improve the hydrophilicity of diamond wire.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] In a first aspect, the present invention provides a coating comprising a modified acrylic resin, 2-hydroxyethyl methacrylate, 1-hydroxycyclohexyl phenyl ketone, plant polyphenols, nanocellulose and ethyl acetate;

[0006] The mass percentage of modified acrylic resin is 0.1%-3%, the mass percentage of 2-hydroxyethyl methacrylate is 0.1%-3%, the mass percentage of 1-hydroxycyclohexyl phenyl ketone is 2%-3%, the mass percentage of plant polyphenols is 0.1%-1%, the mass percentage of nanocellulose is 0.1%-1%, and the mass percentage of ethyl acetate is 89%-97.6%.

[0007] As an optional embodiment, the plant polyphenols are one or more of dopamine, tannic acid, epicatechin gallate and epigallocatechin gallate.

[0008] As an optional embodiment, the plant polyphenol is tannic acid.

[0009] As an optional embodiment, the nanocellulose is one or more of cellulose nanocrystals, bacterial nanocellulose, and cellulose nanofibers.

[0010] As an optional embodiment, the nanocellulose is cellulose nanocrystals.

[0011] In a second aspect, the present invention provides a coating preparation method for preparing the coating in any one of the first aspect, comprising the following steps:

[0012] Adding 89% to 97.6% by mass of ethyl acetate, 0.1% to 3% by mass of modified acrylic resin, 0.1% to 3% by mass of 2-hydroxyethyl methacrylate, and 2% to 3% by mass of 1-hydroxycyclohexyl phenyl ketone into a container respectively, and stirring to form an intermediate dispersed solution;

[0013] 0.1%-1% by mass of plant polyphenols and 0.1%-1% by mass of nanocellulose are added to the intermediate dispersed solution, and the coating is obtained after stirring.

[0014] As an optional embodiment, before the intermediate dispersed solution is formed after stirring, the method further includes: heating the solution in the container to 40° C.-60° C. in a water bath.

[0015] In a third aspect, the present invention provides a coating application method, wherein the coating in any one of the first aspects is applied to a diamond wire coating.

[0016] As an optional implementation, the following steps are included:

[0017] The coating is applied on the surface of the diamond wire with nickel plating, and the coating applied on the diamond wire is cured by ultraviolet light, and after cleaning and drying, a coating of the coating is formed outside the nickel plating layer of the diamond wire.

[0018] As an optional implementation, the thickness of the coating is 1 μm-3 μm.

[0019] The coating provided by the invention comprises modified acrylic resin, 2-hydroxyethyl methacrylate, 1-hydroxycyclohexyl phenyl ketone, plant polyphenols, nanocellulose and ethyl acetate; the mass percentage of the modified acrylic resin is 0.1%-3%, the mass percentage of 2-hydroxyethyl methacrylate is 0.1%-3%, the mass percentage of 1-hydroxycyclohexyl phenyl ketone is 2%-3%, the mass percentage of plant polyphenols is 0.1%-1%, the mass percentage of nanocellulose is 0.1%-1%, and the mass percentage of ethyl acetate is 89%-97.6%. The coating provided by the invention can be coated on the surface of nickel-plated diamond wire to improve the hydrophilicity of the surface of the nickel-plated diamond wire, thereby improving the liquid carrying capacity of the diamond wire. The improvement of the liquid carrying capacity of the diamond wire can avoid the use of or reduce the wetting agent in the cutting liquid, and further solve the problems of difficult defoaming and high cost caused by low surface tension and high concentration of wetting agent. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0021] Figure 1 A schematic diagram of a coating application method provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The processing of single crystal silicon rods into silicon wafers generally adopts the method of diamond wire combined with cutting fluid. The surface of the diamond wire is reinforced by plating metal nickel, which makes the surface of the diamond wire hydrophobic, affecting the ability of the diamond wire to carry liquid and reducing the effect of the cutting fluid. Among them, the cutting fluid generally includes surface active components such as wetting, lubrication, defoaming, and cleaning. The wetting component can ensure that the diamond wire carries the cutting liquid into the cutting slit. The lubrication, cleaning and other components can play a role in reducing the line marks and wire breakage rate of the silicon wafer in the cutting slit. The defoaming component can solve the problem of excessive foam caused by the use of wetting components with low surface tension. However, since the surface of the diamond wire is a hydrophobic nickel metal layer, a wetting agent with low surface tension must be used to ensure the liquid carrying effect. With the development of thin film wire, the cutting slit is getting narrower and narrower, and the concentration of the wetting component is getting higher and higher. In addition, low surfactant agents will cause foam problems and increase the amount of defoaming components. The cost of wetting and defoaming is high. The increase in the amount of these two will greatly increase the overall cost.

[0024] In view of this, the present invention provides a coating, comprising modified acrylic resin, 2-hydroxyethyl methacrylate, 1-hydroxycyclohexyl phenyl ketone, plant polyphenols, nanocellulose and ethyl acetate; the mass percentage of the modified acrylic resin is 0.1%-3%, the mass percentage of 2-hydroxyethyl methacrylate is 0.1%-3%, the mass percentage of 1-hydroxycyclohexyl phenyl ketone is 2%-3%, the mass percentage of plant polyphenols is 0.1%-1%, the mass percentage of nanocellulose is 0.1%-1%, and the mass percentage of ethyl acetate is 89%-97.6%. The coating provided by the present invention can be coated on the surface of nickel-plated diamond wire, improves the hydrophilicity of the surface of the nickel-plated diamond wire, thereby improving the liquid carrying capacity of the diamond wire, reducing the amount of wetting components and defoaming components in the cutting liquid, and saving costs.

[0025] An embodiment of the present invention provides a coating, including modified acrylic resin, 2-hydroxyethyl methacrylate, 1-hydroxycyclohexyl phenyl ketone, plant polyphenols, nanocellulose and ethyl acetate; the mass percentage of the modified acrylic resin is 0.1%-3%, the mass percentage of 2-hydroxyethyl methacrylate is 0.1%-3%, the mass percentage of 1-hydroxycyclohexyl phenyl ketone is 2%-3%, the mass percentage of plant polyphenols is 0.1%-1%, the mass percentage of nanocellulose is 0.1%-1%, and the mass percentage of ethyl acetate is 89%-97.6%.

[0026] Among them, modified acrylic resin refers to a class of resins that are modified by chemical or physical methods to improve their performance or meet specific application requirements. Modified acrylic resins can be modified by adding nanoparticles, blending with other resins, introducing functional monomers, etc., so as to obtain different physical and chemical properties. Modified acrylic resins mainly include epoxy-modified acrylic resins and silicone-modified acrylic resins. Among them, epoxy-modified acrylic resins are introduced into acrylic resins to improve the adhesion, chemical resistance and strength of the resin, while improving flexibility. Silicone-modified acrylic resins are introduced into siloxane structures to improve the heat resistance, weather resistance and color and gloss retention of the resin, and are suitable for high temperature environments and high-demand coatings. Adding modified acrylic resins to the coating can enhance the adhesion of the coating and make it better adhere to the surface of the diamond wire. The modified acrylic resin has high hardness and durability, and can enhance the scratch resistance and anti-pollution performance of the coating. Modified acrylic resins also have excellent transparency and gloss, which can make the coating surface brighter and smoother. In addition, modified acrylic resins can increase the hardness of the coating, making it more resistant to abrasion and scratches.

[0027] The amount of modified acrylic resin added should be appropriate. Excessive modified acrylic resin will significantly increase the viscosity of the coating system. This high-viscosity coating is difficult to spread evenly on the surface of the diamond wire. According to the principles of fluid mechanics, the flow resistance of high-viscosity fluids is large, and it is not easy to form a smooth coating, which can easily cause uneven coating thickness. Moreover, with the excessive increase in resin content, the cross-linking density between molecules is too high, which reduces the flexibility of the coating. According to the principles of material mechanics, the elastic deformation range of materials with high cross-linking density is reduced. When the diamond wire is bent or stretched by external force, the stress generated inside the coating cannot be effectively dispersed through the elastic deformation of the molecular chain, which can easily cause the coating to crack. In addition, excessive modified acrylic resin will also increase the cost and time of the cross-linking reaction, reducing production efficiency. If the amount of modified acrylic resin added is too small, during the drying process of the coating, due to the lack of sufficient film-forming substances, a continuous and complete coating network structure cannot be formed, making the interaction between molecules weak, and it is difficult to build an effective protective barrier on the surface of the diamond wire. Local coating leakage or the overall coating being too thin may occur. In addition, adding too little modified acrylic resin will also result in insufficient adhesion of the coating on the surface of the diamond wire. In actual use, when the diamond wire is subjected to external forces such as vibration and friction, the coating will easily fall off the surface of the diamond wire, and long-term protection and performance improvement functions cannot be achieved.

[0028] Among them, 2-hydroxyethyl methacrylate, referred to as HEME monomer, has a high reactivity of carbon-carbon double bonds in the 2-hydroxyethyl methacrylate molecule during the polymerization reaction. When the polymerization reaction occurs, its double bonds can react with the unsaturated bonds in its modified acrylic resin to form a cross-linked structure. This cross-linked structure can increase the density and complexity of the coating molecular network, thereby enhancing the hardness and chemical stability of the coating. In addition, the hydroxyl group in the 2-hydroxyethyl methacrylate molecule is a strong polar functional group. According to the principle of like dissolves like, it can form hydrogen bond interactions with water molecules, thereby improving the hydrophilicity of the coating, thereby helping to improve the liquid carrying capacity of the diamond wire, making it easier for liquids such as cutting fluid to adhere to the surface of the diamond wire and improving cutting efficiency. Excessive addition of 2-hydroxyethyl methacrylate may cause the cross-linking density of the coating to be too high. Too high a cross-linking density will cause the flexibility of the coating to be severely reduced, and it will become hard and brittle. When the amount of 2-hydroxyethyl methacrylate added is too small, the number of monomers that can participate in cross-linking in the polymerization reaction of the coating is limited, and a cross-linked network structure of sufficient density cannot be formed. Insufficient cross-linking will result in the coating's hardness and chemical stability not being effectively improved. When facing chemical corrosive media or physical friction, the coating's molecular structure is easily destroyed and cannot effectively protect the diamond wire. In addition, a small amount of 2-hydroxyethyl methacrylate added means that there are fewer sites in the coating that can form hydrogen bonds with water molecules, and the insufficient number of hydrophilic functional groups will result in the coating's hydrophilicity improvement effect not being obvious, and the diamond wire's ability to carry liquid cannot be effectively improved.

[0029] Among them, 1-hydroxycyclohexyl phenyl ketone, also known as hydroxycyclohexane phenyl ketone, photoinitiator 184 or UV-184; adding photoinitiator 184 to the coating can increase the curing speed of the coating. It can be understood that photoinitiator 184 can quickly trigger a chemical reaction under ultraviolet light, thereby accelerating the curing speed of the coating, so that the coating can be quickly cured on the surface of the diamond wire. In addition, photoinitiator 184 can also improve the thermal stability and chemical stability of the coating, and can maintain its performance under various processing and storage conditions, and increase the storage time of the coating. On the one hand, excessive addition of photoinitiator 184 will increase the production cost of the coating. On the other hand, excessive photoinitiator 184 will cause the coating to react too quickly during the ultraviolet light curing process. The excessive reaction speed will cause the solvent and other small molecules in the coating to be wrapped by the rapidly curing coating before they can evaporate and escape. These small molecules trapped in the coating will form defects such as bubbles or pinholes, which seriously affect the quality of the coating. If the amount of photoinitiator 184 added is too little, the polymerization reaction rate will be low and the coating will not be fully cured in a short time, which will result in incomplete curing of the coating and affect the hardness, wear resistance and adhesion of the coating.

[0030] Among them, plant polyphenols usually contain multiple phenolic hydroxyl groups in their molecular structure, which give plant polyphenols antioxidant properties. From the perspective of the redox reaction principle, phenolic hydroxyl groups can provide hydrogen atoms and react with free radicals, thereby terminating the oxidation chain reaction caused by free radicals and protecting other components in the coating from oxidative damage. At the same time, the phenolic hydroxyl groups of plant polyphenols can form hydrogen bonds with water molecules to increase the hydrophilicity of the coating surface. In addition, plant polyphenols can also interact with other components in the coating (such as modified acrylic resins, nanocellulose, etc.) through hydrogen bonds, van der Waals forces, etc., to synergistically improve the comprehensive performance of the coating, improve the liquid carrying capacity of the diamond wire, and make the cutting liquid better attached and distributed on the surface of the diamond wire, thereby improving the cutting effect. When the amount of plant polyphenols added is too much, it is easy for molecular aggregation to occur in the coating system or excessive interaction with other components. This excessive interaction will destroy the original stable state of the coating system, leading to precipitation, flocculation and other phenomena. For example, if the hydrogen bonding between plant polyphenol molecules is too strong, the molecules will aggregate to form larger particles, precipitate from the solution, and make the coating uneven. Applying such uneven coating will lead to uneven coating quality. Some areas may have defects due to excessive plant polyphenol content, affecting the overall performance of the coating. If the amount of plant polyphenol added is too small, the number of phenolic hydroxyl groups is limited, the effect on improving the hydrophilicity of the coating surface is weak, and the synergistic effect with other ingredients is not obvious. It is difficult to improve the liquid carrying capacity of the diamond wire, and it is impossible to solve the problems related to the cutting fluid, resulting in poor performance improvement of the diamond wire during the cutting process.

[0031] Adding nanocellulose nanocrystals to the coating can improve the mechanical properties of the coating, such as wear resistance and scratch resistance. Specifically, cellulose nanocrystals have a unique nanoscale size and a rod-like structure with high crystallinity. From the perspective of material reinforcement principle, its nanoscale size enables it to be evenly dispersed in the coating system. During the coating formation process, these nanocrystals can serve as a reinforcing phase and form a good interface with the polymer matrix (such as modified acrylic resin, etc.) in the coating. On the one hand, it is interconnected with polymer molecules through physical adsorption and chemical bonding (such as hydrogen bonding), increasing the internal force of the coating; on the other hand, its rod-like structure with high crystallinity can effectively bear external forces. When the coating is subjected to external forces such as tension, bending or shear, cellulose nanocrystals can disperse stress like steel bars in concrete, thereby improving the strength and hardness of the coating. At the same time, the evenly distributed nanocrystals can also improve the microstructure of the coating, fill the gaps between polymer molecules, and make the coating denser, thereby improving the bonding force between the coating and the surface of the diamond wire, and enhancing the adhesion and durability of the coating.

[0032] Ethyl acetate is used as a solvent to dissolve other ingredients and coordinate the performance of each ingredient. Ethyl acetate is an excellent organic solvent with polar and non-polar parts in its molecular structure, which enables it to interact with various ingredients in the coating. For organic polymers such as modified acrylic resin and 2-hydroxyethyl methacrylate, the non-polar part of ethyl acetate can interact with the non-polar segments of polymer molecules and dissolve them through van der Waals forces; while for ingredients such as plant polyphenols and nanocellulose, the polar part of ethyl acetate can interact with their polar functional groups to promote their dispersion. Ethyl acetate has moderate volatility. After the coating is applied, as the solvent evaporates, other ingredients in the coating gradually gather and solidify to form a coating. In addition, its volatilization process can take away some small molecular impurities in the coating, which helps to improve the purity and quality of the coating. At the same time, it provides convenience for the construction of the coating, so that the coating can be evenly spread on the surface of the diamond wire and form a smooth coating.

[0033] The coating provided by the embodiment of the present invention can participate in the curing reaction by adding plant polyphenols rich in hydroxyl groups, and at the same time, play a role in improving the hydrophilicity of the coating. In addition, in order to increase the mechanical properties of the coating, nanocellulose is also introduced to improve the coating performance from the nanomaterial level. Nanomaterials have the advantages of small size effect, quantum effect, surface effect, etc., which can effectively improve the performance of the material, and nanocellulose also has a large number of hydroxyl groups, which can participate in the reaction while further improving the hydrophilicity of the coating.

[0034] In the above embodiments, plant polyphenols can be selected from one or more of dopamine, tannic acid, epicatechin gallate and epigallocatechin gallate. Specifically, tannic acid can be used as plant polyphenols. Tannic acid has significant hydrophilicity, and the phenolic hydroxyl groups therein can form hydrogen bonds with water molecules. Due to its structural advantages, more effective hydrogen bonding sites can be formed on the coating surface, promoting the adsorption and spreading of water molecules, effectively improving the ability of diamond wire to carry liquid, and solving wetting agent-related problems better than other plant polyphenols. In addition, tannic acid can synergize with modified acrylic resins, nanocellulose and other ingredients through multiple forces to enhance the cohesion and microstructural stability of the coating, optimize adhesion and mechanical properties, and can be well integrated into the system without affecting the overall stability and performance.

[0035] In the above embodiment, nanocellulose can be one or more of cellulose nanocrystals, bacterial nanocellulose, and cellulose nanofibers. Preferably, nanocellulose can use cellulose nanocrystals. Cellulose nanocrystals have a nanometer-level size, and its typical size range is between tens of nanometers and hundreds of nanometers. This small size allows it to be evenly dispersed in the coating system. In the coating formation process, it can be used as a reinforcing phase to form a good interface with the polymer matrix (such as modified acrylic resin) in the coating. Because of its small size, large specific surface area, and large contact area with polymer molecules, it can effectively connect polymer molecules through physical adsorption and chemical bonding (such as hydrogen bonds) to increase the force inside the coating. In addition, cellulose nanocrystals are a rod-like structure with high crystallinity. This structure is like a tiny "rebar", which can effectively bear external forces and disperse stress when the coating is subjected to external forces such as tension, bending or shearing. For example, when the diamond wire is subjected to external forces such as friction during cutting, the cellulose nanocrystals in the coating can prevent the generation and expansion of cracks, improve the strength and hardness of the coating, and thus better protect the diamond wire. Compared with other shapes or nanocellulose with lower crystallinity, this rod-shaped high crystallinity structure has obvious advantages in enhancing mechanical properties. In addition, cellulose nanocrystals can also fill the gaps between polymer molecules. During the drying and curing process of the coating, the nanocrystals are evenly distributed in the polymer matrix, occupying the gaps between molecules, making the microstructure of the coating more dense. The dense coating structure can improve the bonding force between the coating and the surface of the diamond wire, enhance the adhesion of the coating, and prevent the penetration of foreign substances (such as moisture, oxygen, etc.), thereby improving the durability of the coating.

[0036] In addition, an embodiment of the present invention further provides a coating preparation method, which is used to prepare the coating in any one of the above embodiments, comprising the following steps:

[0037] Adding 89% to 97.6% by mass of ethyl acetate, 0.1% to 3% by mass of modified acrylic resin, 0.1% to 3% by mass of 2-hydroxyethyl methacrylate, and 2% to 3% by mass of 1-hydroxycyclohexyl phenyl ketone into a container respectively, and stirring to form an intermediate dispersed solution;

[0038] 0.1%-1% by mass of plant polyphenols and 0.1%-1% by mass of nanocellulose are added to the intermediate dispersed solution, and the coating is obtained after stirring.

[0039] Wherein, before forming the intermediate dispersed solution after stirring, the solution in the container can also be heated to 40° C.-60° C. in a water bath.

[0040] Example 1

[0041] 89% by mass of ethyl acetate, 3% by mass of modified acrylic resin, 3% by mass of 2-hydroxyethyl methacrylate and 3% by mass of 1-hydroxycyclohexyl phenyl ketone were added into a container, the solution in the container was heated to 40° C. in a water bath, and an intermediate dispersed solution was formed after sufficient stirring, and then 1% by mass of plant polyphenols and 1% by mass of nanocellulose were added to the intermediate dispersed solution, and the coating was obtained after sufficient stirring again.

[0042] Example 2

[0043] 90.9% by mass of ethyl acetate, 2.5% by mass of modified acrylic resin, 2.5% by mass of 2-hydroxyethyl methacrylate and 2.7% by mass of 1-hydroxycyclohexyl phenyl ketone were added into a container, the solution in the container was heated to 45° C. in a water bath, and an intermediate dispersed solution was formed after sufficient stirring, and then 0.7% by mass of plant polyphenols and 0.7% by mass of nanocellulose were added to the intermediate dispersed solution, and the coating was obtained after sufficient stirring again.

[0044] Example 3

[0045] 92.5% by mass of ethyl acetate, 2% by mass of modified acrylic resin, 2% by mass of 2-hydroxyethyl methacrylate and 2.5% by mass of 1-hydroxycyclohexyl phenyl ketone were added into a container, the solution in the container was heated to 50° C. in a water bath, and an intermediate dispersed solution was formed after sufficient stirring, and then 0.5% by mass of plant polyphenols and 0.5% by mass of nanocellulose were added to the intermediate dispersed solution, and the coating was obtained after sufficient stirring again.

[0046] Example 4

[0047] 94.1% by mass of ethyl acetate, 1.5% by mass of modified acrylic resin, 1.5% by mass of 2-hydroxyethyl methacrylate and 2.3% by mass of 1-hydroxycyclohexyl phenyl ketone were added into a container, the solution in the container was heated to 55° C. in a water bath, and an intermediate dispersed solution was formed after sufficient stirring, and then 0.3% by mass of plant polyphenols and 0.3% by mass of nanocellulose were added to the intermediate dispersed solution, and the coating was obtained after sufficient stirring again.

[0048] Example 5

[0049] 97.6% by mass of ethyl acetate, 0.1% by mass of modified acrylic resin, 0.1% by mass of 2-hydroxyethyl methacrylate and 2% by mass of 1-hydroxycyclohexyl phenyl ketone were added into a container, the solution in the container was heated to 60° C. in a water bath, and an intermediate dispersed solution was formed after sufficient stirring, and then 0.1% by mass of plant polyphenols and 0.1% by mass of nanocellulose were added to the intermediate dispersed solution, and the coating was obtained after sufficient stirring again.

[0050] In addition, an embodiment of the present invention further provides a coating application method, which applies the coating in any one of the above embodiments to a diamond wire coating.

[0051] In the above embodiment, the coating application method includes the following steps:

[0052] The coating is applied on the surface of the diamond wire with nickel plating, and the coating applied on the diamond wire is cured by ultraviolet light, and after cleaning and drying, a coating of the coating is formed outside the nickel plating layer of the diamond wire.

[0053] In the above embodiment, the thickness of the coating layer may be 1 μm-3 μm. If the coating layer thickness is too small, the durability will be poor, while if the coating layer thickness is too thick, the rigidity will be reduced.

[0054] You can refer to Figure 1 When the coating is applied to the surface of the diamond wire, the diamond wire can enter the warm water tank for cleaning after nickel plating in the electroplating area, clean the components of the electroplating solution, and then pass through the coating tank for coating, and then enter the ultraviolet curing area for cross-linking and curing. The ultraviolet light wavelength can be selected to be 200-450nm, the power is 4kW, and the diamond wire travel speed is 2-5 seconds / meter. Finally, the unreacted substances are washed away in the warm water tank, and the desired finished product is obtained after drying.

[0055]

[0056] The above table shows the performance of the coating and the diamond wire (the performance of the diamond wire with or without coating) as the components in the coating change. It can be seen from the table that plant polyphenols and nanocellulose have a significant impact on the performance of the coating and the performance of the diamond wire. The coating provided in the embodiment of the present invention can significantly improve the performance of the coating and the diamond wire.

[0057] The coating provided by the embodiment of the present invention comprises modified acrylic resin, 2-hydroxyethyl methacrylate, 1-hydroxycyclohexyl phenyl ketone, plant polyphenols, nanocellulose and ethyl acetate; the mass percentage of the modified acrylic resin is 0.1%-3%, the mass percentage of 2-hydroxyethyl methacrylate is 0.1%-3%, the mass percentage of 1-hydroxycyclohexyl phenyl ketone is 2%-3%, the mass percentage of plant polyphenols is 0.1%-1%, the mass percentage of nanocellulose is 0.1%-1%, and the mass percentage of ethyl acetate is 89%-97.6%. The coating provided by the embodiment of the present invention can be coated on the surface of nickel-plated diamond wire to improve the hydrophilicity of the surface of nickel-plated diamond wire, thereby improving the liquid carrying capacity of diamond wire. The improvement of the liquid carrying capacity of diamond wire can avoid the use of or reduce the wetting agent in the cutting liquid, and further solve the problem of difficult defoaming and high cost caused by low surface tension and high concentration of wetting agent.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A coating, characterized in that: Including modified acrylic resin, 2-hydroxyethyl methacrylate, 1-hydroxycyclohexyl phenyl ketone, plant polyphenols, nanocellulose and ethyl acetate; The mass percentage of the modified acrylic resin is 0.1%-3%, the mass percentage of the 2-hydroxyethyl methacrylate is 0.1%-3%, the mass percentage of 1-hydroxycyclohexyl phenyl ketone is 2%-3%, the mass percentage of the plant polyphenols is 0.1%-1%, the mass percentage of the nanocellulose is 0.1%-1%, and the mass percentage of the ethyl acetate is 89%-97.6%.

2. The coating according to claim 1, characterized in that The plant polyphenols are one or more of dopamine, tannic acid, epicatechin gallate and epigallocatechin gallate.

3. The coating according to claim 2, characterized in that The plant polyphenol is tannic acid.

4. The coating according to claim 3, characterized in that The nanocellulose is one or more of cellulose nanocrystals, bacterial nanocellulose and cellulose nanofibers.

5. The coating according to claim 4, characterized in that The nanocellulose is cellulose nanocrystal.

6. A method for preparing a coating, for preparing the coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: Adding 89% to 97.6% by mass of ethyl acetate, 0.1% to 3% by mass of modified acrylic resin, 0.1% to 3% by mass of 2-hydroxyethyl methacrylate, and 2% to 3% by mass of 1-hydroxycyclohexyl phenyl ketone into a container respectively, and stirring to form an intermediate dispersed solution; 0.1%-1% by mass of plant polyphenols and 0.1%-1% by mass of nanocellulose are added to the intermediate dispersed solution, and the coating is obtained after stirring.

7. The coating preparation method according to claim 6, characterized in that: Before the intermediate dispersed solution is formed after stirring, the method further comprises: heating the solution in the container to 40° C.-60° C. in a water bath.

8. A coating application method, characterized in that: The coating material described in any one of claims 1 to 5 is applied to diamond wire coating.

9. The coating application method according to claim 8, characterized in that: The following steps are involved: The coating is applied on the surface of the diamond wire with nickel plating, and the coating applied on the diamond wire is cured by ultraviolet light, and after cleaning and drying, a coating of the coating is formed outside the nickel plating layer of the diamond wire.

10. The coating application method according to claim 9, characterized in that: The coating has a thickness of 1 μm-3 μm.

Citation Information

Patent Citations

  • Functional modification method for surface and interface of material based on polyphenol compounds

    CN105218847A

  • UV finish paint as well as preparation method and application thereof

    CN115746676A

  • Cellulose nanocrystal super-hydrophilic coating, preparation method and application

    CN116622268A

  • Photocurable coating composition for building materials, cured coat, and substrate with cured coat

    JP2022125559A